658 The Use of AlliumTM Stents in the Management of Ureteric Strictures. (19th August 2022) - Skinner, H; Please, H; Young, M; Khan, A; Burbidge, S; Biyani, CS
Abstract: Aim: Stents are widely used in the management of ureteric strictures but require changes every 6–12 months and stent related symptoms are commonly reported. Allium TM ureteric stents are large calibre, metallic stents that aim to reduce the incidence of stent-related complications, with an indwelling time up to three years. These were introduced within our local hospital trust for patients requiring frequent stent changes and this study aims to review the early use of Allium TM stents and associated complications. Method: An electronic database of patients was searched for records including the words "Allium stent" between 01/01/17–01/01/21. The resulting patient electronic records were then interrogated to extract data. Results: 13 patients were included in data analysis. Mean age was 62.7 years and male:female ratio was 6:7. 5 underwent antegrade insertion and 8 retrograde. 3 were inserted under local anaesthetic and 10 under general. Median follow-up time was 459 days. No cases of renal deterioration were noted, and no patients sought medical attention with pain or irritative symptoms. The majority remained in situ, however one patient reported spontaneous passage of the stent; and one patient later required a nephrectomy, necessitating stent removal. Three patients developed post-operative urinary tract infections (two requiring hospital admission); two patients required further intervention for urolithiasis causing stent blockage; and two patients died from other disease processes prior to analysis. Conclusions: There are clear advantages in reducing repeated admission and anaesthesia for patients. Initial results demonstrate good patency and tolerability of Allium TM stents though further investigation is required to analyse the long-term benefits.